2021
DOI: 10.3390/foods10123099
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Lactic Acid Bacteria and Their Potential Function in Dietetics: The Food–Gut-Health Axis

Abstract: Fermented dairy products are the good source of different species of live lactic acid bacteria (LAB), which are beneficial microbes well characterized for their health-promoting potential. Traditionally, dietary intake of fermented dairy foods has been related to different health-promoting benefits including antimicrobial activity and modulation of the immune system, among others. In recent years, emerging evidence suggests a contribution of dairy LAB in the prophylaxis and therapy of non-communicable diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 162 publications
1
32
0
1
Order By: Relevance
“…Other studies have recently reported this association in children with obesity [43][44][45][46][47]. Behind the excess of simple sugars instead of foods rich in nutrients, several other mechanisms have been reported, such as derangements in the calcium homeostasis, insulin secretion, satiety and satiation and gut-microbiota when the intake of dairy products is low [45,48,49]. In our cohort a low intake of nuts and cereals was associated with an increased risk of being overweight and obese.…”
Section: Dietary Factors Associated With the Risk Of Obesitysupporting
confidence: 61%
“…Other studies have recently reported this association in children with obesity [43][44][45][46][47]. Behind the excess of simple sugars instead of foods rich in nutrients, several other mechanisms have been reported, such as derangements in the calcium homeostasis, insulin secretion, satiety and satiation and gut-microbiota when the intake of dairy products is low [45,48,49]. In our cohort a low intake of nuts and cereals was associated with an increased risk of being overweight and obese.…”
Section: Dietary Factors Associated With the Risk Of Obesitysupporting
confidence: 61%
“…In mice [ 2 , 33 ], chicken [ 25 ], and humans [ 2 , 34 ], LAB probiotic strains have shown significant protection against a various number of infectious diseases [ 17 , 19 , 20 , 21 , 25 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Intranasal and oral pretreatment with LAB strains proved effective in protecting mice against influenza virus infection but did not protect against severe weight loss disease [ 43 , 44 ]. Furthermore, various trials have shown that preventing a cold in healthy elders and extending the survival time for mice with influenza has shown positive results [ 2 , 19 , 35 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various trials have shown that preventing a cold in healthy elders and extending the survival time for mice with influenza has shown positive results [ 2 , 19 , 35 , 45 ]. Many studies found that some novel probiotic isolates increase innate and acquired immunity [ 46 , 47 , 48 ], increasing antiviral defenses [ 25 , 43 , 44 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“… Lactobacillus species as probiotic bacteria are being used in many dairy products to provide health benefits ( 13 ). One of the beneficial effects of Lactobacillus species as probiotics is the inhibition of pathogen infection.…”
Section: Introductionmentioning
confidence: 99%